Straightforward and direct access to β-seleno- amines and sulfonylamides via the controlled addition of phenylselenomethyllithium (LiCH2SePh) to imines. Issue 51 (18th December 2020) - Senatore, Raffaele; Malik, Monika; Touqeer, Saad; Listro, Roberta; Collina, Simona; Holzer, Wolfgang; Pace, Vittorio
Abstract: The transfer of a α-methyl phenylseleno carbanion to variously functionalized N -aryl and N- sulfonyl imines is reported. The fast selenium-lithium exchange conducted on a diselenoacetal with n -BuLi enables the generation of the attacking homologative nucleophile under chemoselective conditions preserving concomitant potentially sensitive functionalities to the lithiating conditions. Uniformly high yields were observed, thus establishing a valuable and conceptually simple approach to the title compounds. Graphical abstract: Image 1